Palladium supported ionic liquid phase catalyst (Pd@SILP-PS) for room temperature Suzuki-Miyaura cross-coupling reaction - More, S.; Jadhav, S; Salunkhe, R.; Kumbhar, A. (Molecular Catalysis, 2017)
A new Pd-SILP based on amino functionalized imidazolium ionic liquid immobilized on Merrifield resin (Pd@SILP-PS) has been synthesized. The catalyst was characterized by different techniques like FT-IR, SEM-EDS, TEM, TGA-DTA and XPS. The catalyst has shown to be highly active in Suzuki-Miyaura cross-coupling reaction of various aryl halides and aryl boronic acids in ethanol at room temperature. The activity of catalyst and the nature of product were highly dependent on the type of the solvent used, as well as the substituents present on the aryl halides. The protic polar solvent ethanol gave desired cross-coupling product in good to excellent yields at room temperature. However the aprotic polar solvent THF gave homocoupling product. The catalyst showed at least five times recyclability without a decrease in product yield.
Keywords: Immobilization; Ionic liquid; Palladium; SILP; Suzuki-Miyaura reaction